Pergeseran Komunikasi Media Lama Menuju Media Baru - Lovia Evanne (Universitas Muhammadiyah Kotabumi, 2021)
It doesn't feel like the shift in communication from old media to new media is moving fast. This can be seen from the increasing number of smartphone users. Smartphone users began to flood rural areas, including Tanah Abang Village, Lampung. Almost all residents of Tanah Abang Village use smart phones as a means of communication. Old media can be recognized by the use of print media (newspapers, magazines, tabloids) and electronic media (radio and television). The flow of technological developments, which include new media, is also marked by the old media undergoing transformation. Currently, social media is also a new media category such as Facebook, Instagram, YouTube and others. It is said that the media is new because the information is distributed through the social media. The purpose of this study was to determine the phenomenon of the shift of old media communication to new media in Tanah Abang Village, Lampung and the benefits of the shift of old media to new media. The research method used is descriptive qualitative. The results of the study were 1) the residents of Tanah Abang Lampung Village mostly used new media in the form of social media. 2) the shift of old media communication to new media is felt to be of great use to increase knowledge that is not bound by time and space. The conclusion from the research on the Shift of Old Media Communication to New Media in Tanah Abang Village Lampung is 1) Tanah Abang Lampung Village residents use new media in the form of social media and the positive impact of shifting old media communication to new media is to increase knowledge that is without time and space boundaries.2) The transition process using new media which is considered expensive and difficult to use because of the needs of the times.